2014
DOI: 10.1039/c3dt53234h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of magnesium complexes containing sterically demanding N,N′-bis(aryl)amidinate ligands

Abstract: Reaction between N,N′-bis(aryl)amidines and di-n-butylmagnesium affords magnesium amidinates, where the steric bulk of the ligand influences both the solid state and solution behaviour of these complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…The magnesium metal centers in these complexes were held together by two l 2 -O bridging by the aminoalkoxy oxygen atoms and are in a pentacoordinate state with a distorted trigonal bipyramidal geometry. The Mg-N bond lengths with amidinate ligands range between 2.0864(13) and 2.1776 (16) Å which are in a same range of Mg-N bond lengths exhibited by dimeric complexes such as bis[bis(N, N-diisopropylacetamidinato)-magnesium] (2.0904(17) Å) and bis [bis(1-tert-butyl-3-ethylacetamidinato)magnesium] (2.097(2) Å) [5(a)] as well as pentacoordinate magnesium amidinate complexes such as [Mg(MesN{C(Ph)}NMes) 2 (THF)] (2.1157(11) Å) and [Mg (MesN{C(Dmp)}NMes) 2 (THF)] (2.1193(15) Å) [17]. The bond lengths between magnesium and the dmamp-N atom in the complexes 1-3 were recorded as 2.2665 (13), 2.2564(14), and 2.2729 (13) Å, respectively, which are in close range of those of similarly bridged dimeric magnesium complexes [Mg(dmamp) [11].…”
Section: X-ray Crystal Structure Of 1-3mentioning
confidence: 99%
“…The magnesium metal centers in these complexes were held together by two l 2 -O bridging by the aminoalkoxy oxygen atoms and are in a pentacoordinate state with a distorted trigonal bipyramidal geometry. The Mg-N bond lengths with amidinate ligands range between 2.0864(13) and 2.1776 (16) Å which are in a same range of Mg-N bond lengths exhibited by dimeric complexes such as bis[bis(N, N-diisopropylacetamidinato)-magnesium] (2.0904(17) Å) and bis [bis(1-tert-butyl-3-ethylacetamidinato)magnesium] (2.097(2) Å) [5(a)] as well as pentacoordinate magnesium amidinate complexes such as [Mg(MesN{C(Ph)}NMes) 2 (THF)] (2.1157(11) Å) and [Mg (MesN{C(Dmp)}NMes) 2 (THF)] (2.1193(15) Å) [17]. The bond lengths between magnesium and the dmamp-N atom in the complexes 1-3 were recorded as 2.2665 (13), 2.2564(14), and 2.2729 (13) Å, respectively, which are in close range of those of similarly bridged dimeric magnesium complexes [Mg(dmamp) [11].…”
Section: X-ray Crystal Structure Of 1-3mentioning
confidence: 99%
“…6,[9][10][11][12][13][14]36 In the course of synthesising potassium silylamide precursors for this study, crystals of [{K[μ-N-(Si t BuMe 2 ) 2 ]} 2 ] ∞ (6) were obtained and identified by single crystal XRD (Fig. As the reaction of [K{N(Si t BuMe 2 ) 2 }] n or 5b with allylmagnesium chloride is slow and gives poor yields of 1 (see above), we selected methylmagnesium iodide as an alternative starting material, which has been extensively used in the literature as a reagent for the preparation of L-Mg-X and L-Mg-R complexes.…”
Section: Reactions Of Methylmagnesium Iodide With Silylamines and Potmentioning
confidence: 99%
“…4,5 Bochmann and co-workers have shown that cationic magnesium complexes with bulky amido ligands such as [Mg(N″)(Et 2 O) 3 ][BAr F ] (N″ = {N(SiMe 3 ) 2 } − , BAr F = {B(C 6 F 5 ) 4 } − ) can act as potent ring opening polymerisation catalysts, 7 an industrially significant process in which Chisholm and others have shown magnesium catalysts have great promise. 10 Multidentate ligands such as guanidinates, [9][10][11] amidinates 12 and β-diketiminates 6, [9][10][11]13,14 dominate N-donor magnesium chemistry and there are relatively few examples of monodentate complexes. 10 Multidentate ligands such as guanidinates, [9][10][11] amidinates 12 and β-diketiminates 6, [9][10][11]13,14 dominate N-donor magnesium chemistry and there are relatively few examples of monodentate complexes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the very bulky triisopropylphenyl group induces steric strain and significantly different Mg-N bond lengths are observed. 9(2) - [20] [Mg{(Dipp-N) 2 C-Cy} 2 ] 4 205.9 207.5 - [21] [Mg{(Dipp-N) 2 C-C 6 H 3 -3,5-Me 2 } 2 ] 4 204.8 206.3 - [21] [ [9] [(thf ) 2 Mg(Mes-NNN-Mes) 2 ], [10] and [(Et 2 O)Mg(Dipp-NNN-Dipp) 2 ] [11] with Mg-N distances varying between 211.7 to 221.7 pm for penta-and hexa-coordinate metal atoms. Different Mg-N bond lengths have also been observed for magnesium-bound sym- [11] [(thf) 2 Mg(Tol-NNN-Tol) 2 ] 6 214.8(3) 221.7(2) - [9] [(thf) 2 Mg(Mes-NNN-Mes) 2 ] 6 217.8(2) 218.…”
Section: Introductionmentioning
confidence: 99%